Acoustic streaming, the "small invention" of cyanobacteria? - Koiller, Jair (2010)
Micro-engineering pumping devices without mechanical parts appeared "way back" in the early 1990's. The working principle is acoustic streaming. Has Nature "rediscovered" this invention 2.7 Gyr ago? Strands of marine cyanobacteria Synechococcus swim 25 diameters per second without any visible means of propulsion. We show that nanoscale amplitude vibrations on the S-layer (a crystalline shell outside the outer membrane present in motile strands) and frequencies of the order of 0.5-1.5 MHz (achievable by molecular motors), could produce steady streaming slip velocities outside a (Stokes) boundary layer. Inside this boundary layer the flow pattern is rotational (hence biologically advantageous). In addition to this purported "swimming by singing", we also indicate other possible instantiations of acoustic streaming. Sir James Lighthill has proposed that acoustic streaming occurs in the cochlear dynamics, and new findings on the outer hair cell membranes are suggestive. Other possibilities are membrane vibrations of yeast cells, enhancing its chemistry (beer and bread, keep it up, yeast!), squirming motion of red blood cells along capillaries, and fluid pumping by silicated diatoms.